Prevalence of Post-traumatic Stress Symptoms and Its Associations With Quality of Life, Demographic and Clinical Characteristics in COVID-19 Survivors During the Post-COVID-19 Era - Yuan, Yuan; Liu, Zi-Han; Zhao, Yan-Jie; Zhang, Qinge; Zhang, Ling; Cheung, Teris; Jackson, Todd; Jiang, Guo-Qing; Xiang, Yu-Tao (Frontiers in Psychiatry, 2021)
Background: The prevalence of posttraumatic stress symptoms (PTSS) in COVID-19 survivors is unclear. This study examined the prevalence of PTSS and its association with quality of life (QOL) among COVID-19 survivors during the post-COVID-19 era in China. Methods: This was a comparative, cross-sectional study. PTSS, depressive symptoms, and QOL were assessed with standardized instruments. Results: A total of 134 COVID-19 survivors and 214 non-infected controls (healthy controls hereafter) were recruited. Among COVID-19 survivors, the PTSS prevalence was 18.66% (95%CI: 11.98%-25.34%), which was significantly higher than that (5.61%, 95%CI: 2.50%-8.71%) of healthy controls (P<0.001). After controlling for covariates, an analysis of covariance (ANCOVA) showed that COVID-19 survivors had a higher PTSS total score than did healthy controls (F (1, 348) =4.664, P=0.032). A separate ANCOVA revealed there were no significant differences in overall QOL between COVID-19 survivors with and without PTSS (F (1, 348) =1.067, P=0.304). A multiple logistic regression analysis showed that more severe depressive symptoms were significantly associated with PTSS in COVID-19 survivors (OR=1.425, P<0.001). Conclusions: PTSS were more severe in COVID-19 survivors compared to healthy controls in the post-COVID-19 era. Considering their negative impact on daily life and functional outcomes, regular assessment and appropriate treatments of PTSS should be conducted in COVID-19 survivors.